Impact of Trade Costs on Trade: Empirical Evidence from Asian Countries - Prabir De (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
Findings of this paper have important policy implications for Asian countries seeking to expand trade. Addressing rising auxiliary shipping charges as well as the overall rise in shipping costs may require serious consideration by regulators and policymakers that wish to further promote trade in Asia. In addition, if improvements in the quality of infrastructure in LDCs continue to lag behind those in more developed countries, their share in world trade is likely to decline.
Keywords: F1; 330; Trade Facilitation; Trade Cost; Trade Liberalisation